2007
DOI: 10.1016/j.cub.2007.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Parental Contribution to Early Plant Zygotic Development

Abstract: Hybrid vigor or heterosis results from the combination of genetically distant genomes at fertilization, and as well as being of major commercial importance, it is held to contribute significantly to fitness [1]. Activation of the paternal genome marks the transition from maternal to zygotic control of development, but a reported delay of paternal-genome activation in flowering plants [2-4] and animals [5, 6] excludes heterosis from impacting on very early development. We have analyzed the allele-specific expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 26 publications
4
62
0
1
Order By: Relevance
“…However, the origin of these maternal transcripts is unclear: since most expression studies only measure steady state mRNA levels, it is usually not possible to determine whether a maternal transcript detected in the embryo is gametophytic (deposited prior to fertilization), zygotic (produced de novo after fertilization), or both. In fact, several paternal alleles (endogenous and transgenic) are expressed soon after fertilization (Weijers et al, 2001;Scholten et al, 2002;Kö hler et al, 2005;Meyer and Scholten, 2007;Bayer et al, 2009). In addition, many early embryo lethal phenotypes segregate as classical zygotic mutations, suggesting that both maternal and paternal alleles are active (Tzafrir et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, the origin of these maternal transcripts is unclear: since most expression studies only measure steady state mRNA levels, it is usually not possible to determine whether a maternal transcript detected in the embryo is gametophytic (deposited prior to fertilization), zygotic (produced de novo after fertilization), or both. In fact, several paternal alleles (endogenous and transgenic) are expressed soon after fertilization (Weijers et al, 2001;Scholten et al, 2002;Kö hler et al, 2005;Meyer and Scholten, 2007;Bayer et al, 2009). In addition, many early embryo lethal phenotypes segregate as classical zygotic mutations, suggesting that both maternal and paternal alleles are active (Tzafrir et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However mechanisms causing zygotic activation and controlling karyogamy remain unknown and might differ between fertilization of the egg cell and fertilization of the central cell. With a few exceptions (Bayer et al, 2009;Leroy et al, 2007;Springer et al, 2000), the importance of parentally inherited transcripts has not been established and when the onset of transcription and translation takes place is unclear (Meyer and Scholten, 2007;Vielle-Calzada et al, 2000;Weijers et al, 2001). A global delay of paternal genome expression is expected to make early seed development independent from the presence of the paternal genome.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies in Arabidopsis (Vielle-Calzada et al, 2000) and maize (Grimanelli et al, 2005) have shown that for many genes, no transcripts derived from the paternal allele can be detected during the first few days after fertilization, suggesting widespread maternal controls. However, the early presence of paternally derived transcripts has been demonstrated for several loci (Meyer and Scholten, 2007;Weijers et al, 2001), suggesting that the requirement for the initiation of paternal transcriptional activity might differ on a gene-by-gene basis. Ueli Grossniklaus (Institute of Plant Biology, University of Zurich, Switzerland) presented a collaborative project with Daniel Grimanelli to study the regulation of paternal genome activation.…”
Section: Chromatin Reprogramming and Pluripotencymentioning
confidence: 99%